2015
DOI: 10.1590/s1413-70542015000200010
|View full text |Cite
|
Sign up to set email alerts
|

PRODUCTION OF ginger vinegar

Abstract: Vinegar is a food of condiments group that have great use in the food industry. This study aimed to evaluate the effects of parameters of the acetic fermentation process in the production of ginger vinegar. A suspension of ginger rhizomes with 12% of starch was subjected to enzymatic hydrolysis process to obtain hydrolyzed with 85.6% of glucose. After the alcoholic fermentation the wine was obtained with 40.3% ethanol. The acetic fermentation process of ginger alcoholic solution followed a completely randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
1
4
0
2
Order By: Relevance
“…Corn starch has an amount of protein in its composition smaller than unconventional starches, this fact possibly gives it a greater thermal stability. The results for thermogravimetric analysis are in agreement with the literature [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Thermogravimetry (Tg)supporting
confidence: 90%
See 1 more Smart Citation
“…Corn starch has an amount of protein in its composition smaller than unconventional starches, this fact possibly gives it a greater thermal stability. The results for thermogravimetric analysis are in agreement with the literature [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Thermogravimetry (Tg)supporting
confidence: 90%
“…Ginger (Zingiber officinale) is a popular spice that is cultivated and used for medicinal purposes, mainly in India; however, it is also highly cultivated in tropical and subtropical areas such as China, Indonesia and Nigeria [8-9-10]. It has organic acids, such as citric, malic, oxalic, succinic and tartaric acids, as well as gingerol, which is responsible for its pungent taste [11]. Ginger rhizomes contain approximately 11.4% starch; the amylose content (18-30%) is similar to that of potato starch and higher than that of cassava starch [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In a study on quality control of commercial acetic acid fermentation, MARQUES et al ( 2010) observed higher levels of reduced dry extract of 48.8 g/L, 38.3 g/L, and 23.4 g/L for orange vinegar with honey, orange and tangerine vinegar and corn vinegar. In this study, the results observed may be related to the filtration method, as there are different filtration processes in the vinegar industry used to clarify the product but can change the concentration and the mineral content (LEONEL et al, 2015;OZTURK et al, 2015). Mangaba fruit is a potential source of minerals such as calcium, zinc, phosphorus, and iron (NARAIN et al, 2018;BRAMONT et al, 2018).…”
Section: Mangaba Vinegarmentioning
confidence: 92%
“…Vinegar production from this fruit is therefore a challenge, and the use of the enzyme pectinase is an alternative to enable alcoholic fermentation in a semi-solid matrix. Pectinolytic enzymes assist in the extraction of aromatic components and increase alcohol yield, as the hydrolysis of pectin increases the amount of reducing sugars available for fermentation in the medium (LEONEL et al, 2015;SPINOSA et al, 2016;RODA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Zoche et al(2015) studied Brazilian grape vinegar production by spontaneous fermentation in different fermentation conditions. Leonel et al (2015) evaluated the effects of acid fermentation parameters on the production of ginger vinegar; they reached high-quality vinegar with high yield. Xiong et al (2016) stated that Chinese vinegar is mainly made from grain crops in a long manufacturing period.…”
Section: Fermentation Productionmentioning
confidence: 99%